Complement Inhibitors Vitronectin and Clusterin Are Recruited from Human Serum to the Surface of Coronavirus OC43-Infected Lung Cells through Antibody-Dependent Mechanisms - Candace R. Fox; Griffith D. Parks (Viruses, 2021)
Little is known about the role of complement (C’) in infections with highly prevalent circulating human coronaviruses such as OC43, a group of viruses of major public health concern. Treatment of OC43-infected human lung cells with human serum resulted in C3 deposition on their surfaces and generation of C5a, indicating robust C’ activation. Real-time cell viability assays showed that in vitro C’-mediated lysis of OC43 infected cells requires C3, C5 and C6 but not C7, and was substantially delayed as compared to rapid C’-mediated killing of parainfluenza virus type 5 (PIV5)-infected cells. In cells co-infected with OC43 and PIV5, C’-mediated lysis was delayed, similar to OC43 infected cells alone, suggesting that OC43 infection induced dominant inhibitory signals. When OC43-infected cells were treated with human serum, their cell surfaces contained both Vitronectin (VN) and Clusterin (CLU), two host cell C’ inhibitors that can alter membrane attack complex (MAC) formation and C’-mediated killing. VN and CLU were not bound to OC43-infected cells after treatment with antibody-depleted serum. Reconstitution experiments with purified IgG and VN showed that human antibodies are both necessary and sufficient for VN recruitment to OC43-infected lung cells–novel findings with implications for CoV pathogenesis.